CK2 Molecular Targeting-Tumor Cell-Specific Delivery of RNAi in Various Models of Cancer - Janeen H. Trembley; Betsy T. Kren; Md. Joynal Abedin; Rachel I. Vogel; Claire M. Cannon; Gretchen M. Unger; Khalil Ahmed (MDPI AG, 2017)
Protein kinase CK2 demonstrates increased protein expression relative to non-transformed cells in the majority of cancers that have been examined. The elevated levels of CK2 are involved in promoting not only continued proliferation of cancer cells but also their resistance to cell death; thus, CK2 has emerged as a plausible target for cancer therapy. Our focus has been to target CK2 catalytic subunits at the molecular level using RNA interference (RNAi) strategies to achieve their downregulation. The delivery of oligonucleotide therapeutic agents warrants that they are protected and are delivered specifically to cancer cells. The latter is particularly important since CK2 is a ubiquitous signal that is essential for survival. To achieve these goals, we have developed a nanocapsule that has the properties of delivering an anti-CK2 RNAi therapeutic cargo, in a protected manner, specifically to cancer cells. Tenfibgen (TBG) is used as the ligand to target tenascin-C receptors, which are elevated in cancer cells. This strategy is effective for inhibiting growth and inducing death in several types of xenograft tumors, and the nanocapsule elicits no safety concerns in animals. Further investigation of this therapeutic approach for its translation is warranted.